김치가 청장년 및 노인의 유리기 생성 및 산화억제에 미치는 영향 - 김종현 외; 류재두; 송영옥 (Korean journal of community nutrition, 2002)
This study was performed to investigate the effect of kimchi intake on free radical and oxidative substance production in young adults and the elderly. Daily kimchi intake by people in their twenties (n = 93, 20 to 29 years old) and over sixty-five (n = 143, over 65 years old) in M city were surveyed and blood was drawn to analyze the free radicals in their plasma. The average amount of kimchi intake by the subjects was 115.8 $±$ 91.7 g. The amount of kimchi intake of those in their twenties (106.1 $±$ 80.6 g) was significantly lower than that of those over sixty-five (125.5 $±$ 102.9 g, p < 0.05). Concentrations of total free radicals and OH radicals were 27 and 33% greater respectively, in those over sixty-five than in those in their twenties, indicating that more free radicals were produced by the older group. The concentration of GSH was not signiacantly different in the two groups, but that of GSSG in the over sixty-five age group was 53% greater than in the twenties group, which resulted in a 35% reduction in GSH/GSSG in the elderly group. TBARS concentration in the over sixty-five group was 26% greater than that of the twenties group. In order to see the effect of kimchi intake on free radical production, subjects in same age group were divided into two sub groups-the mean over and the mean under groups-according to the average amount of kimchi intake, which was 115.8 g. The total free radicals, the OH radicals, the GSH, the GSSG, and the GSH/GSSG in the twenties group were not significantly different in the two kimchi intake groups. However, those in the over sixty-five group were significantly different. The concentration of total free radicals and OH radicals of the mean over group were 21 and 26% lower respectively, than those of the mean ova. group (p < 0.05). The GSH and GSH/GSSG of the mean ova. groups were higher by 8 and 12%, respectively. The correlation coefficient between the kimchi intake and the total free radicals was -0.1862 (p < 0.05) and that for GSH/GSSG was 0.1861 (p < 0.05). In conclusion, the production of free radicals and oxidative substances increased with age, and kimchi seemed to retard this phenomena.